Management of Tourism Villages Using the Triple Bottom Line Concept - Sandy Sandy; Murtafia murtafia; Gina lucita (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Tourism villages have emerged as a viable option for local economic development and community welfare. As a result, the development of tourist villages has become a national initiative. The purpose of this research is to examine the accomplishments of a tourist village's management using the triple bottom line concept. Nonongan Selatan Tourism Village in North Toraja Regency and Kolesawangan Tourism Village in Tana Toraja Regency were chosen as research sites. The data for this study was gathered using a qualitative method, including interviews, observation, and document analysis. The findings of this study show that the Tourism Village Concept, as applied to Lembang Nonongan Selatan Village, which emphasizes people's daily lives, and Lembang Kole Sawangan Village, which emphasizes historical tourist destinations, has reflected the Triple Bottom Line Concept, which is measured in three areas: profit, people, and planet. This demonstrates that the concept of a tourist village is consistent with the government's goals, which are to improve the quality of life and welfare of the community while maintaining environmental quality. Keywords: Tourism village, sustainable economy, triple bottom line